Forcing of the wintertime atmospheric circulation by the multidecadal fluctuations of the North Atlantic ocean - Peings, Y; Magnusdottir, G (Environmental Research Letters, 2014)
The North Atlantic sea surface temperature exhibits fluctuations on the multidecadal time scale, a phenomenon known as the Atlantic Multidecadal Oscillation (AMO). This letter demonstrates that the multidecadal fluctuations of the wintertime North Atlantic Oscillation (NAO) are tied to the AMO, with an opposite-signed relationship between the polarities of the AMO and the NAO. Our statistical analyses suggest that the AMO signal precedes the NAO by 10-15 years with an interesting predictability window for decadal forecasting. The AMO footprint is also detected in the multidecadal variability of the intraseasonal weather regimes of the North Atlantic sector. This observational evidence is robust over the entire 20th century and it is supported by numerical experiments with an atmospheric global climate model. The simulations suggest that the AMO-related SST anomalies induce the atmospheric anomalies by shifting the atmospheric baroclinic zone over the North Atlantic basin. As in observations, the positive phase of the AMO results in more frequent negative NAO - and blocking episodes in winter that promote the occurrence of cold extreme temperatures over the eastern United States and Europe. Thus, it is plausible that the AMO plays a role in the recent resurgence of severe winter weather in these regions and that wintertime cold extremes will be promoted as long as the AMO remains positive. © 2014 IOP Publishing Ltd.